Formation of Bio-based Derived Dicalcium Silicate Ceramics via Mechanochemical Treatment: Physical, XRD, SEM and FTIR Analysis - Yunus, Siti Nur Hazwani; Khor, Shing Fhan; Johar, Banjuraizah; Adzali, Nur Maizatul Shima; Jakfar, Nur Hazlinda; Cheng, Ee Meng; Mohd Tarmizi, Emma Ziezie; Talib, Zainal Abidin (UniMAP, 2023)
Beta-dicalcium silicate plays important role in modern technology, but its tendency for polymorphic transformation results in the dusting phenomenon is a major challenge. Therefore, mechanochemical treatment is used to reduce the particle size to retain the stability of the polymorph. Herein, in this study, pure dicalcium silicate ceramics of ²- monoclinic structure with P 121/c1 space group were synthesized using calcium oxide and silicate powders derived from calcined eggshells and rice husks, respectively. The powders were mixed in a 2:1 molar ratio by mechanochemical treatment and heat-treated in the air at temperatures ranging from 900°C to 1100°C for 2 hours. The results reveal that pure beta-dicalcium silicate formed at 1100°C without adding stabilizers. The properties of the pristine and sintered bodies were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). SEM revealed that the grain and pore size increase with rising sintering temperatures. FTIR spectra indicate the existence of Si-O bonds in -4 4 SiO tetrahedrons on all the samples. The sample sintered at 1000°C attains the lowest bulk density (1.2463 g/cm3), whereas the apparent porosity is the highest (62.5). The reason for this trend is due to the decomposition of carbonate into CO2 gas. The densification onset for the sample sintered at 1100°C as the bulk density rises and grain size achieves 6.06 ¼m. This study further explains the effect of sintering temperatures on the physical, structural, and morphological of Ca2SiO4 which would be also useful for further optimization of its use.